Valorização de coprodutos das cadeias produtivas de biocombustiveis - Fernanda Gomes de Mendonca (2019)
In this work it was investigated routes for the use of byproducts of different biofuels chains: aqueous acid fraction (AAF) and biochar obtained in bio-oil production, and glycerin obtained as byproduct of biodiesel. Chapter 2 presents the results on the recovery of carboxylic acids from aqueous medium aiming to apply this method in AAF from bio-oil using montmorillonite clay (Mt). Titrations and TOC analyses showed that these acids can be adsorbed in high amounts by Mt clay, close to 50 mmol g clay -1. XRD analyses suggested that a portion of acid molecules is intercalated in the interlayer space of Mt. TG-MS and BET indicated that acetic and propionic acids can be easily recovered from Mt, leading to a delamination of the clay, with mesopores formation and an increase of surface area. Experiments using AAF from bio-oil indicated that Mt can be used in the removal and recovery of small organic acids present in this complex mixture. Chapter 3 shows the results on the application of Fe/C composites obtained from AAFcombined to an iron-rich waste in photo-Fenton reactions. Due to its high acidity, AAF is capable to extract Fe3+ of mining wastes and, after a thermal treatment, take to the formation of composites. All the obtained composites showed efficiency in photo-Fenton reactions to oxidizemethylene blue, presenting high activities even in neutral medium.Chapter 4 presents the study on the effects of thermal treatment of biochar, which were analyzed considering changes on surface area, functional groups and reactivity. Characterizations showed that thermal treatment improved the surface area, modifying surface groups of biochar. The obtained materials were studied in adsorption of dyes and also in reactions of oxidation of aqueous sulfide. Chapter 5 shows the studies on the combination of glycerin, biodiesel byproduct, with afatty acid commonly present in different vegetable oils, oleic acid, to obtain new materials. Citric acid was used in the reactions as an interconnecting agent, and solid and liquid products were obtained. Liquid products presented the property to form and to break emulsions with pH variation. The solid products showed to be like a reticulated polymeric gel with high capacity to absorb water and other different species, being able to reduce oxidizing species that can be present in aqueous medium.